Incorporation of relative cerebral blood flow into CT perfusion maps reduces false 'at risk' penumbra. (30th September 2017) - Peretz, Shlomi; Orion, David; Last, David; Mardor, Yael; Kimmel, Yotam; Yehezkely, Shelly; Lotan, Eyal; Itsekson-Hayosh, Ze'ev; Koton, Sylvia; Guez, David; Tanne, David
Abstract : Purpose: The region defined as 'at risk' penumbra by current CT perfusion (CTP) maps is largely overestimated. We aimed to quantitate the portion of true 'at risk' tissue within CTP penumbra and to determine the parameter and threshold that would optimally distinguish it from false 'at risk' tissue, that is, benign oligaemia. Methods: Among acute stroke patients evaluated by multimodal CT (NCCT/CTA/CTP) we identified those that had not undergone endovascular/thrombolytic treatment and had follow-up NCCT. Maps of absolute and relative CBF, CBV, MTT, TTP and Tmax as well as summary maps depicting infarcted and penumbral regions were generated using the Intellispace Portal (Philips Healthcare, Best, Netherlands). Follow-up CT was automatically co-registered to the CTP scan and the final infarct region was manually outlined. Perfusion parameters were systematically analysed – the parameter that resulted in the highest true-negative-rate (ie, proportion of benign oligaemia correctly identified) at a fixed, clinically relevant false-negative-rate (ie, proportion of 'missed' infarct) of 15%, was chosen as optimal. It was then re-applied to the CTP data to produce corrected perfusion maps. Results: Forty seven acute stroke patients met selection criteria. Average portion of infarcted tissue within CTP penumbra was 15%±2.2%. Relative CBF at a threshold of 0.65 yielded the highest average true-negative-rate (48%), enabling reduction of the false 'at risk' penumbral region by half. Conclusions: Applying a relative CBF threshold on relative MTT-based CTP maps can significantly reduce false 'at risk' penumbra. This step may help to avoid unnecessary endovascular interventions.